Study of advanced ion conducting polymers by relaxation, diffusion and spectroscopy NMR methods - Jardón Álvarez, Daniel (2016)
Advances on secondary lithium ion batteries imply the use of solid polymer electrolytes, which represent a promising solution to improve safety issues in high energy density batteries. Through dissolution of lithium salts into a polymeric host, such as poly(ethylene oxide) (PEO), ion conducting polymers are obtained. The Li+ ions will be localized in the proximity of the oxygen atoms in the PEO chains and thus, their motion strongly correlated with the segmental reorientation of the polymer. Nuclear magnetic resonance (NMR) spectroscopy, translational diffusion coefficients and transverse relaxation times (T2) contribute to the understanding of the involved structures and the ongoing dynamical processes in ionic conductivity. Nuclei with different motional freedom can present different T2 times. T2xT2 exchange experiments enable studying exchange processes between nuclei from different motional regimes. In this work, three different ion conducting polymers were studied. First, PEG was doped with different amounts of LiClO4. 7Li NMR relaxometry measurements were done to study dynamical behavior of the lithium ions in the amorphous phase. All samples presented two lithium types with clearly differentiated T2 times, indicating the presence of two regions with different dynamics. The mobility and consequently the T2 times, increases with temperature. It was observed, that the doping ratio strongly influences the dynamics of the lithium ions, as the amount of crystalline PEG is reduced while increasing the polarity of the sample. A local maximum of the mobility was observed for y = 8. With the T2xT2 exchange experiments exchange rates between both lithium sites were quantified. Second, the triblock copolymer PS-PEO-PS doped with LiTFSI was studied with high resolution solid state NMR techniques as well as with 7Li relaxometry measurements. T1ρ and spin diffusion measurements gave insight on the influence of the doping and the PS/PEO ratio on the mobility of the different segments and on interdomain distances of the lamellar phases. Third, multiple quantum diffusion measurements were applied on poly(ethylene glycol) distearate (PEGD) doped with LiClO4. Therefore, triple quantum states of the 3/2 nucleus 7Li were excited. After optimizing the experimental procedure, it was possible to obtain reliable diffusion coefficients using triple quantum states.